Pengaruh Masker Kesemek terhadap Kecerahan Kulit - Khoerunnisa, Echa Nabila; Ambarwati, Neneng Siti Silfi (Universitas Negeri Jakarta, 2021)
This study aims to analyze whether there is any effect of persimmon mask to brighten skin. This study applied quasi experimental research methods, skin color chart as an instrumental that use to evaluation the skin color. Sampling was done by purposive sampling where sampling was conducted based on the physical appearance or characteristic of the population in accordance with the purpose of the research. The total of the sample was 10 people, divided into two treatment groups. Five people used persimmon masks as the research group and the other five people used papaya masks as the control group. Each group received 8 treatments for four weeks and the treatment was done twice a week .After obtaining the data, analysis requirement test by normality test using Lilliefors test and two test of variance homogeneity. The result for group A Lhitung < Ltabel is 0,221 < 0,337, so the experiment A have a normal distribution. Whereas experiment B obtained Lhitung < Ltabel, 0,163 < 0,337 so the experiment B are normally distributed. For testing the homogeneity of two variances the writer used F test, Fhitung < Ftabel is 2,19< 6,39, this means the data are homogenous. The writer also applied T test average of two directions which indicated t= 2,72 at the signigicance level of α = 0,05 and Ttable= 1,86 so, the null hypothesis (Ho) is rejected and (Hi) received. It means that the type of facial skin care using soursop leaf persimmon mask totally has influence to brighten the skin.